Atrial fibrillation following transcatheter atrial septal defect closure: a systematic review and meta-analysis. Issue 15 (21st October 2021) - Himelfarb, Jonah Daniel; Shulman, Healey; Olesovsky, Christopher James; Rumman, Rawan K; Oliva, Laura; Friedland, Joshua; Farrell, Ashley; Huszti, Ella; Horlick, Eric; Abrahamyan, Lusine
Abstract : Objective: The ostium secundum atrial septal defect (ASD) is among the most common congenital cardiac anomalies diagnosed in adulthood. A known complication of transcatheter ASD closure is the development of new-onset atrial fibrillation and flutter (AFi/AFl). These arrhythmias confer an increased risk of postoperative stroke, thrombus formation and systemic emboli. This systematic review examines the burden of de novo AFi/AFl in adults following transcatheter closure and seeks to identify risk factors for AFi/AFl development. Methods: Studies were identified by a search of MEDLINE, EMBASE and Cochrane databases from inception until 29 April 2020. A meta-analysis of AFi/AFl incidence was performed using a random-effects model. Results: A total of 31 studies met inclusion criteria, comprising 4788 adult patients without a history of AFi/AFl. Twenty-three studies were included in quantitative synthesis and demonstrated an overall incidence rate of 1.82 patients per 100 person-years of follow-up (I 2 =83%). In studies that enrolled only patients ≥60 years old, the incidence was 5.21 patients per 100 person-years (I 2 =0%). Studies with follow-up duration ≤2 years reported an incidence of 4.05 per 100 person-years (I 2 =55%) compared with a rate of 1.19 per 100 person-years (I 2 =85%) for studies with follow-up duration >2 years. Conclusions: The incidence of new-onset AFi/AFl is relatively low following transcatheter closure of secundum ASDs. The rate of de novo AFi/AFl, however, was significantly higher in elderly patients. Shorter follow-up time was associated with a higher reported incidence of AFi/AFl.